Understanding Work in WA Public Schools: 2019 Report to the State School Teachers Union of WA - Fitzgerald, Scott; McGrath-Champ, Susan; Wilson, Rachel; Stacey, Meghan (State School Teachers Union of WA, 2019)
This report present and analyses the findings of the Understanding Work in WA Public Schools survey, undertaken with the SSTUWA in 2018. Although teachers in WA public schools maintain a core focus on matters directly related to teaching and learning, as found in the NSW iteration of this survey (McGrath-Champ et al., 2018), they face new and encroaching requirements relating to administration and accountability. While teaching and learning activities account for the bulk of their daily activities, there is also evidence that many teachers are struggling to preserve this student focus in light of new work activities that require additional hours, create new work demands, and place significant personal burdens upon them. Teachers, Program coordinators, Head of Departments/ Head of Learning Areas, Deputy Principals, Principals and Consultants place the most value on activities which are perceived to be directly related to their teaching and to students’ learning. In particular, respondents identified: planning and teaching lessons; meeting students’ learning needs; and communicating with students about their learning, lives and wellbeing as being particularly important. However, and again as with the NSW survey results, teachers do not value administrative work which is perceived to be intruding upon this core focus, and is experienced as time consuming, cumbersome and concerned with compliance. Such work includes that associated with accreditation requirements; the collection, analysis and reporting of data; and compliance with state policies. There has been significant growth in overall hours over the past five years; 72.7% of survey respondents report an increase in their hours since the implementation of a range of policy changes including the further roll out of the Independent Public Schools (IPS) initiative, the Student Centred Funding Model and one‐line budget to all WA public schools. Classroom teachers most commonly report working upwards of 50 hours per week, which, as in NSW, places teachers’ work in the category of ‘very long’ working hours.